ANALYSIS OF FACTORS AFFECTING E-COMMERCE CUSTOMER PURCHASE DECISION - Rini Astuti; delyana pulungan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The purpose of this study was to determine and analyze the effect of Promotion, Ease of Use and Trust on Purchase Decisions for Shopee E-Commerce Customers in Medan City. The approach used in this study is an associative approach. The population in this study were E-Commerce Shopee Customers in Medan City as many as 100 customers while the sample in this study used Nonprobability sampling or Saturated Sampling as many as 100 people. The data collection technique used in this study is a questionnaire/questionnaire. The data analysis technique in this study uses Multiple Linear Regression Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. Data processing in this study uses the support of the SPSS software program. The results of this study prove that partially Promotion (X1) has a significant effect on Purchase Decisions (Y), Partially Ease of Use (X2) has a significant effect on Purchase Decisions (Y), Partial Trust has a significant effect on Purchase Decisions (Y). And Simultaneously Promotion, Ease of Use and Trust have a positive and significant impact on Purchase Decisions for Shopee E-Commerce Customers in Medan City